Inventarisasi Tumbuhan Obat di Desa Alue Tampak, Kecamatan Kaway XVI, Kabupaten Aceh Barat - Nasrianti Syam (Universitas Muhamadiyah Manado, 2022)
Indonesia is one of the countries with the highest biodiversity in the world. Medicinal plants are plants that have properties or contain certain compounds to cure a disease. This study was conducted in Alue Tampak Village, Kaway XVI District, West Aceh Regency. This study aims to determine the plants used by the village community, the parts of the plants used and the diseases treated. The method used is the purposive sampling method which consists of 20 respondents. The results of the interview found 28 plants used by the people of Alue Tampak Village. The most widely used part of the plant is the leaves as much as 68%, the least is the rhizome and flower parts, namely 7%. Plants used as medicine for fever and headaches are 25%.